From tradition to modernity: The role of smart villages in reshaping agricultural communities and sustainable development - Hassan, Nugroho; Arista, Nor Isnaeni Dwi (Holistic: Journal of Tropical Agriculture Sciences, 2025)
Background: Improving the welfare of farmers in rural areas can be done through various methods, one of which is Smart Village. The Smart Village concept has been introduced as an initiative that integrates advanced technology and sustainable agricultural practices. This research aims to evaluate the impact of implementing the Smart Village concept on changes in farmer welfare. Methods: This research used literature reviews approach to collect and analyze data from various previous studies related to the implementation of Smart Villages and their impact on farmer welfare. Findings: The analysis results show that Smart Village contributes significantly to increasing agricultural productivity through the use of smart agricultural technology, such as automatic irrigation systems and the use of big data for weather predictions and soil analysis. In addition, better access to markets and price information has helped farmers increase their bargaining power, which has a direct positive effect on their income. However, the study also points to challenges, including the need for adequate technological training for farmers and large initial investments. Conclusion: The Smart Village concept, through the integration of technology and smart agricultural practices, has proven effective in encouraging changes in the welfare of farmers in rural areas. To maximize its benefits, ongoing support from government and the private sector is needed in the form of training, funding and infrastructure. Novelty/Originality of this article: This study bridges the gap between modern technology and traditional agriculture, exploring how the Smart Village concept can revolutionize rural life. This study opens new avenues for inclusive and competitive rural development by combining digital innovation and sustainable agricultural practices